Manajemen Dana Bantuan Operasional Sekolah untuk Pencapaian Mutu Pembelajaran - Hani Latifah (Jurnal Pendidikan UNIGA, 2017)
Abstract. Bantuan Operasional Sekolah (BOS) and its various polemic has always been a separate topic in education. The problems that arise in the implementation of government policies related to the BOS funds are very complex, both on a regional and national scale. This research uses descriptive method with qualitative approaches in elementary schools in Garut. The collection of data is carried out through observation, interviews, and documentation study. Specifically, the results showed: 1) the implementation of the management of BOS funds at the primary level in Garut has been grounded in legislation and regulations and technical guidelines that apply, but the result is not optimal because of the limited funds received by the school, with BOS the school is only able to meet operational needs daily course, unable to meet for other programs related to the achievement of the quality of schools. 2) The school seeks to prioritize the use of the budget on things that are important that have been designed previously in RKAS. However, in reality the principal difficult to use the funds exactly in accordance with RKAS.The school principal also difficult to innovate because the use of the funds should not be used instead of the 13 components that have been specified in the Technical Handbook (Technical Guidance) use of the funds. 3) are common obstacles and constraints in the implementation of BOS funds in improving the quality of education in elementary school. Primarily associated with insufficient funds for the attainment of quality education with funds sourced from the BOS funds alone. Delays in the distribution of BOS funds be an obstacle big enough and the lack of awareness and understanding of the principals in managing the BOS funds are transparent and accountable. This makes is difficult to increase the quality of education. 4) Step forward improvements that the budget allocation, the principal is attempting to establish priorities, the biggest allocation is to meet the standards development costs educators as well as the process of teaching and learning activities. Kata kunci: manajemen, Bantuan Operasional Sekolah, mutu pembelajaran